2017
DOI: 10.21037/jtd.2017.02.80
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of propofol preconditioning on ischemia-reperfusion injury in human hepatocyte

Abstract: Background: Blood reperfusion after ischemia is the main measure to restore cell function. This study was aimed to explore the effect of propofol on rat and cell models of liver ischemia-reperfusion (I/R) injury, and to investigate its possible mechanism. Methods: Wistar rats were divided into four groups: control group, sham group, I/R group, and propofol group. Human hepatocyte HL7702 was divided into six groups: control group, I/R group and propofol (5, 10, 20 and 40 µmol/L) groups. After the animal and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…It has also been found by multiple research teams that propofol has protective effects against IRI in multiple organs [33,34]. Propofol infusion has also been suggested to have protective effects against renal IRI in rats, but the underlying mechanism is not fully understood [10,13,35]. In the present study, HE staining of IRI-affected rat renal tissue (Fig.…”
Section: +supporting
confidence: 55%
See 1 more Smart Citation
“…It has also been found by multiple research teams that propofol has protective effects against IRI in multiple organs [33,34]. Propofol infusion has also been suggested to have protective effects against renal IRI in rats, but the underlying mechanism is not fully understood [10,13,35]. In the present study, HE staining of IRI-affected rat renal tissue (Fig.…”
Section: +supporting
confidence: 55%
“…In recent years, studies have demonstrated the protective effects of propofol against ischemic injury in the kidneys, liver and heart [9][10][11]. It has been suggested in early studies that propofol protects against opioid-induced hyperresponsiveness of airway smooth muscle during target-controlled infusion anesthesia [12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that propofol inhibits the activity of nuclear transcription factor NF-kβ during ischemia reperfusion injury and reduces the adhesion force of endotheliocytes 16 . In addition, propofol inhibits hydrogen peroxide-induced myocardial apoptosis and attenuates myocardial ischemia reperfusion injury by regulating autophagy-related genes 17 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, due to its phenolic structure, propofol can prevent ischemic/reperfusion injury (13,14). Furthermore, propofol has an anti-oxidative effect in rat cardiomyocytes and macrophages, which is associated with the suppression of oxidative stress-related enzymes including inducible nitric oxide synthase, superoxide dismutase (SOD) and neutrophil cytosolic factor 1.…”
Section: Introductionmentioning
confidence: 99%